PENGARUH ELECTRONIC WORD OF MOUTH, ELECTRONIC SERVICE QUALITY, DAN PERSEPSI HARGA TERHADAP MINAT PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PADA LAYANAN NETFLIX DI KOTA BEKASI - Ardhiyanto, Wira; Rivai P, Agung Kresnamurti; Febrilia, Ika (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This research aims to examine the influence of electronic word of mouth, electronic service quality, price perception, customer satisfaction and repurchase intention. This research uses quantitative research methods. Data collection uses a questionnaire. The subjects in the research were 255 respondents who live in Bekasi, Indonesia. Data analysis uses SPSS and AMOS version 24. The research results prove that the first hypothesis proves that electronic word of mouth has a positive and significant effect on customer satisfaction. The second hypothesis proves that electronic service quality has a positive and significant effect on customer satisfaction. The third hypothesis proves that price perception has a positive and significant effect on customer satisfaction. The fourth hypothesis proves that customer satisfaction has a positive and significant effect on repurchase intention. The fifth hypothesis proving that electronic word of mouth has a positive and significant effect on repurchase intention is rejected. The sixth hypothesis proves that electronic service quality has a positive and significant effect on repurchase intention. The seventh hypothesis proves that price perception has a positive and significant effect on repurchase intention. The eighth hypothesis proving that electronic word of mouth has a positive and significant effect on repurchase intention through customer satisfaction is rejected. The ninth hypothesis proves that electronic service quality has a positive and significant effect on repurchase intention through customer satisfaction. The tenth hypothesis proving that price perceptions have a positive and significant effect on repurchase intention through customer satisfaction is rejected